Kölner Kunst Markt 70. - Kunsthalle Köln, Köln; Art Cologne, Köln (Köln : Kunstmarkt Köln, 1970)
Abrahams, Ivor ; Accardi, Carla ; Adami, Valerio ; Adzak, Roy ; Aeschbacher, Hans ; Akawie, Thomas ; Albers, Josef ; Albert, Hermann ; Alechinsky, Pierre ; Alt, Otmar ; Altenbourg, Gerhard ; Alviani, Getulio ; Andre, Carl ; de Andrea, John ; Antes, Horst ; Anuszkiewicz, Richard ; Arakawa, Shusaku ; Arman ; Arp, Hans (Jean) ; Artschwager, Richard ; Attersee, Christian Ludwig ; Aubertin, Bernard ; Avramidis, Joannis ; Baer, Jo ; Bandau, Joachim ; Bannard, Darby ; Baschlakow, Alexej Iljitsch ; Baselitz, Georg ; Bayrle, Thomas ; Becher, Bernd & Hilla ; Bell, Larry ; Bellmer, Hans ; Bengston, Billy Al ; Beuys, Joseph ; Bill, Max ; Birgfeld, Detlef ; Bochner, Mel ; Böhmler, Claus ; Bohrmann, Karl Friedrich ; Bollinger, Bill ; Bonalumi, Agostino ; Bonato, Victor ; Bonomi, Maria ; Boshier, Derek ; Brecht, George ; Breer, Robert ; Brehmer, Klaus-Peter ; Broodthaers, Marcel ; Brouwn, Stanley ; Brüning, Peter ; Bubenik, Gernot ; Buchholz, Wolff ; Buren, Daniel ; Bury, Pol ; Buthe, Michael ; Calderara, Antonio ; de Camargo, Sergio ; Carder, Malcolm ; Castro, Lourdes ; Ceroli, Mario ; Chaissac, Gaston ; Chamberlain, John ; Chillida, Eduardo ; Christensen, Dan ; Christo ; Clark, Lygia ; Clarke, John Clem ; Colombo, Castro ; Colombo, Gianni ; Copley, William ; Corneille ; Cote, Alan ; Croissant, Michel ; Cruz-Diez, Carlos ; D'Arcangelo ; Dali, Salvador ; Danby, Ken ; Darboven, Hanne ; Davie, Alan ; Davis, Ron ; Deem, George ; Denny, Robyn ; Dibbets, Jan ; Dichgans, Christa ; Diehl, Hans Jürgen ; Dietrich, Hansjoachim ; Dine, Jim ; Distel, Herbert ; Dorazio, Piero ; Dörflinger, Hans ; Dubuffet, Jean ; Duchamp, Marcel ; Duff, John ; Eddy, Don ; Equipo 57 ; Erhardt, Hans Martin ; Ernst, Jimmy ; Ernst, Max ; Errò ; Estève, Maurice ; Ferrer, Rafael ; Filliou, Robert ; etc.
Kölner Kunst Markt 70, Kunsthalle und Kunstverein, Köln, 13. - 18. Oktober 1970
Duits
kunstcatalogus